2015
DOI: 10.1039/c5ra06438d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polyurethane-imide/kaolinite nanocomposite foams

Abstract: A novel polymer/kaolinite nanocomposite based on polyurethane-imide (PUI) foams was prepared by in situ polymerization. The PUI foams were synthesized via the reaction between isocyanate terminated polyimide prepolymers and polyether polyol. The kaolinite was modified with an intercalating agent of potassium carbonate. XRD analyses of the intercalated kaolinite and the PUI/kaolinite nanocomposite foams indicate that both intercalated and exfoliated structures are formed. The cell structure, cell size distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…As a result, it was observed that the samples containing kaolinite and silica are stronger compared to the individual performances . Additionally, Chen et al prepared a new polymer/kaolinite nanocomposite based on polyurethane‐imide foams in their study, and the results showed that the addition of kaolinite to the structure significantly improved the mechanical properties …”
Section: Resultsmentioning
confidence: 99%
“…As a result, it was observed that the samples containing kaolinite and silica are stronger compared to the individual performances . Additionally, Chen et al prepared a new polymer/kaolinite nanocomposite based on polyurethane‐imide foams in their study, and the results showed that the addition of kaolinite to the structure significantly improved the mechanical properties …”
Section: Resultsmentioning
confidence: 99%
“…In this process, the ICT plays an important role in lowering the energy gap. [42][43][44][45] The quantum yields (Φ = 0.41 to Φ = 0.57) of the compounds 2 show higher than compound 1 (Φ = 0.01) with the electron-donating ability of the functional group para to the benzene. We also find that there are slight differences, in this process, this was thought to be the ICT plays an important role in lowering the energy gap.…”
Section: Photo-physical Propertiesmentioning
confidence: 99%
“…The characteristic absorption peaks at 1779, 1360 and 726 cm −1 are assigned to the asymmetric stretching vibration, symmetric stretching vibration and bending vibration of C=O (aromatic imide), respectively . The intensity of the peaks significantly increased with increasing dosage of PMDA, indicating that the imide group was successfully introduced into the PU backbone, and the content in the PU main chains was proved to be close to the dosage of PMDA with high reaction efficiency in our previous work …”
Section: Resultsmentioning
confidence: 70%